Growth curves of developing Siboney females from Cuba, up to 18 months old - Alonso, Á.; Chongo, Bertha; Zamora, A.; Torres, Verena; Noda, Aida C.; Acosta, F. (Cuban Journal of Agricultural Science, 2016)
Growth curves of 1,338 developing Siboney females from Cuba, between 0 and 18 months old, were modeled, in the period 2007-2009, with weights recorded at 0, 4, 8, 12 and 18 months. Curves were divided according to birth season, into rainy and dry seasons. Database was obtained from the information registered in SISCOP software for the studied years. Seven variants of regression models were tested (linear, square linear, cubic linear, square logarithmic, logistic, Gompertz and Richards), for data analysis, and daily weight gains were estimated through the method of square minimums. As statistical criteria for selecting the best adjusted model, the determination coefficient (R2), parameters of models(α, β, γ, δ), mean square of error (MSE), standard error of models (E(α), E(β), E(γ)), E(δ)), model signification and residue analysis were determined. For females born during rainy season, the R2 ranged between 0.94 and 0.97, while those born during dry season, the (R2) ranged between 0.95 and 0.98. It can be concluded that the best adjusted model was the square logarithmic model, with con R2 = 0.98 (born during dry season) and 0.96 (rainy season), with P < 0.001 in every case. The best increases were registered in animals born during dry season and between years. The best performance was registered in 2007. Key words: mathematic models, growth curves, liveweight, bovines